2018
DOI: 10.1021/acs.orglett.8b01099
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Assembly of Polycyclic Molecules from 1,6-Enynes Triggered by Rhodium(III)-Catalyzed C–H Activation

Abstract: An Rh(III)-catalyzed C-H activation of pyrazolones with 1,6-enynes was investigated. The regioselectivity of the C-H activation/alkyne insertion is readily solved by using symmetric enyne coupling partners, and a C-H activation-triggered cascade reaction is realized, which involves alkyne insertion, tautomerization, and double cyclization to offer a class of structurally complex polycyclic architectures. This cascade reaction tolerates a broad substrate scope in high regioselectivity and stereospecificity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…In 2018, Zhang et al [14] accounted for the synthesis of highly stereoselective polycyclic molecules from desymmetrization of 1,6-enynes through Rh-catalyzed CÀ H functionalization of N-aryl pyrazol-5-one approach. This desymmetrizative annulation path was proposed as depicted in Scheme 10, with some exper- imental evidence.…”
Section: 1-annulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Zhang et al [14] accounted for the synthesis of highly stereoselective polycyclic molecules from desymmetrization of 1,6-enynes through Rh-catalyzed CÀ H functionalization of N-aryl pyrazol-5-one approach. This desymmetrizative annulation path was proposed as depicted in Scheme 10, with some exper- imental evidence.…”
Section: 1-annulationsmentioning
confidence: 99%
“…In 2018, Zhang et al [14] . accounted for the synthesis of highly stereoselective polycyclic molecules from desymmetrization of 1,6‐enynes through Rh‐catalyzed C−H functionalization of N‐aryl pyrazol‐5‐one approach.…”
Section: 1‐annulationsmentioning
confidence: 99%
“…The approaches to access them via transition-metal-catalyzed C-H bond activation are particularly impressive, because these products are highly congested scaffolds difficult to access through traditional methods. Zhang's group in 2018 developed an Rh(III)-catalyzed C−H bond activation strategy to assemble pyrazolones with 1,6-enynes to access fused-chromene scaffolds (Scheme 27) [107]. This cascade reaction ranged a broad substrate scope in high regioselectivity and stereospecificity and furnished three new chemical bonds and four chiral centers in a single operation.…”
Section: Catalysts 2019 9 X For Peer Reviewmentioning
confidence: 99%
“…Even if Rh catalysts are expensive, they have unique advantages because of their functional group tolerance, wide range of substrate scope, high activity, and selectivity for synthetic transformations [22][23][24][25][26]. Rh catalysts are used by many researchers in C-H activation reactions [27][28][29]. One kind of Rh catalyst, which contains Cp* (Cp* = 1,2,3,4,5-Pentamethylcyclopentadiene (C 5 Me 5 ) ligands, has been used to catalyze oxidative coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…One kind of Rh catalyst, which contains Cp* (Cp* = 1,2,3,4,5-Pentamethylcyclopentadiene (C 5 Me 5 ) ligands, has been used to catalyze oxidative coupling reactions. For example, Lu et al reported that [Cp*RhCl 2 ] 2 catalyzed the C-H activation of pyrazolones with symmetric 1,6-enynes to obtain functional products in 34%-72% yield [27]. Krieger's team used [Cp*RhCl 2 ] 2 to obtain macrocyclic pyridones in excellent yields, and proposed that the catalyst could become more efficient in redox-neutral processes when the O-pivaloyl hydroxamate is the directing group [28].…”
Section: Introductionmentioning
confidence: 99%